(untitled) (Lex localis - Journal of Local Self-Government, 2025)
In recent years, DNA profiling has become an integral part of the investigative and trial processes as a vital forensic tool and technique. In a court of law, the method and the DNA data provide supporting evidence to establish guilt or innocence beyond a reasonable doubt. With an eye toward improving justice delivery and introducing new forensic methods, this research investigates how the Indian legal system may include DNA profiling and digital DNA evidence. The growing importance of forensic science in criminal investigations and the demand to fill the loopholes in the current DNA evidence legal framework in India motivate this study. The study recognizes the profound influence that DNA technology has had on the field of justice. The study’s overarching goals are to assess DNA forensics in India as it stands right now, catalog the obstacles to its widespread use, and recommend solutions for better integration with judicial processes. In order to gain a thorough understanding of the topic, this study uses a mixed-method approach. Doctrinal method involves reviewing literature and analyzing legal and case law. Empirical method involves collecting data in the context of technological assessment and the efficacy of this innovation. For evaluating the value of DNA evidence in Indian courts, it examines pertinent statutes, rationes decidendi, court rulings, and scientific literature. Furthermore, it delves into the utilization of digital platforms and tools for DNA data management and analysis, showcasing their ability to enhance precision and efficacy. Despite DNA profiling’s substantial contribution to solving complicated criminal cases, as per the finding a number of obstacles, such as inadequate infrastructure, a lack of qualified staff, and worries about data privacy and security, remain. To guarantee the ethical use of DNA technology in India’s justice delivery system, the study finds that the legislative framework needs to be strengthened, worldwide best practices should be adopted, and ethical norms should be promoted. Additionally, for effective incorporation of DNA evidence into the Indian legal system, the research highlights the significance of forensic scientists, legal professionals, and legislators working together.